Use of GelMA for 3D printing of cardiac myocytes and fibroblasts. Issue 1 (15th January 2019) - Koti, Priyanka; Muselimyan, Narine; Mirdamadi, Eman; Asfour, Huda; Sarvazyan, Narine A
Aim: To 3D print heart tissue, one must understand how the main two types of cardiac cells are affected by the printing process.Materials & methods: Effects of gelatin methacryloyl (GelMA) concentration, extruder pressure and duration of UV exposure on survival of cardiac myocytes and fibroblasts were examined using lactate dehydrogenase and LIVE/DEAD assays, bioluminescence imaging and morphological assessment.Results & conclusion: Cell survival within 3D printed cardiomyocyte-laden GelMA constructs was more sensitive to extruder pressure and GelMA concentrations than within 3D fibroblast-laden GelMA constructs. Cells within both types of constructs were adversely impacted by the UV curing step. Use of mixed cell populations and enrichment of bioink formulation with fibronectin led to an improvement of cardiomyocyte survival and spreading.